Порівняльний аналіз принципів сімейного права в Україні та державах Західної Європи - Менджул, Марія Василівна; Менджул, М. В.; Mendzhul, Mariia V. (Одеса, 2018)
Досліджене законодавство України та держав Західної Європи, що містить принципи правового регулювання сімейних відносин. Виокремлено спільні та відмінні принципи сімейного права в Україні й Австрії, Бельгії, Німеччині, Нідерландах, Люксембургу, Ліхтенштейні, Монако, Швейцарії. Установлено, що спільними принципами правового регулювання сімейних відносин є принципи державної охорони сім’ї, рівності, пріоритету інтересів дитини, одношлюбності й ін. Надані пропозиції щодо вдосконалення норм Сімейного кодексу України.

The legislation of Ukraine and the countries of Western Europe, which contains the principles of legal regulation of family relations, is studied. The common and distinct principles of family law in Ukraine and Austria, Belgium, Ger many, the Netherlands, Luxemburg, Liechtenstein, Monaco, Switzerland are identified. It was established that the common principles are: state protection of the family, childhood, motherhood, equality, respect for family life, priority of the interests of the child, single-parentage, voluntary marriage, freedom of divorce, etc. At the same time, special principles are established in certain European countries: preservation of family integrity (in Germany); taking into account the will of the child (in Austria); the principle of the prohibition and prevention of domestic violence (in Germany, Monaco), mutual assistance between spouses (in Austria, the Netherlands, Switzerland); the principle of joint and several liability of the spouses for family debts (in the Netherlands). Legislation found in civil law in Monaco is contrary to the principle of equality and restricts the right to marriage. Among the analyzed states of Western Europe, the legislation only of Liechtenstein and Monaco does not recognize same-sex marriages, nor does it regulate the partnership relations between persons of one article. Both in Ukraine and in the states of the European Union, family law principles play an important role; they not only determine the directions of legal regulation of family relations, but also allow to regulate relations in the absence of the relevant legislation, or when the rules of the law are not clearly understood. Proposals for improvement of legislation are proposed, namely, to consolidate in Art. 7 of the Family Code of Ukraine principle of mutual support of spouses and family members.
Менджул М. В. Порівняльний аналіз принципів сімейного права в Україні та державах Західної Європи / М. В. Менджул // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 31. – С. 49-53.
Keywords: принцип; сім’я; сімейні відносини; шлюб; закон; principle; family; family relations; marriage; law; Research Subject Categories::LAW/JURISPRUDENCE